Ion pumps as biological targets for decavanadate - Aureliano, M. (2013)
The putative applications of poly-, oligo- and mono-oxometalates in biochemistry, biology, pharmacology and medicine are rapidly attracting interest. In particular, these compounds may act as potent ion pump inhibitors and have the potential to play a role in the treatment of e.g. ulcers, cancer and ischemic heart disease. However, the mechanism of action is not completely understood in most cases, and even remains largely unknown in other cases. In the present review we discuss the most recent insights into the interaction between mono- and polyoxometalate ions with ion pumps, with a particular focus on the interaction of decavanadate with Ca2+- ATPase. We also compare the proposed mode of action with those of established ion pump inhibitors which are currently in therapeutic use. Of the 18 classes of compounds which are known to act as ion pump inhibitors, the complete mechanism of inhibition is only known for a handful. It has, however, been established that most ion pump inhibitors bind mainly to the E2 ion pump conformation within the membrane domain from the extracellular side and block the cation release. Polyoxometalates such as decavanadate, in contrast, interact with Ca2+- ATPase near the nucleotide binding site domain or at a pocket involving several cytoplasmic domains, and therefore needs to cross through the membrane bilayer. In contrast to monomeric vanadate, which only binds to the E2 conformation, decavanadate binds to all protein conformations, i.e. E1, E1P, E2 and E2P. Moreover, the specific interaction of decavanadate with sarcoplasmic reticulum Ca2+- ATPase has been shown to be non-competitive with respect to ATP and induces protein cysteine oxidation with concomitant vanadium reduction which might explain the high inhibitory capacity of V10, (IC50=15 µM) which is quite similar to the majority of the established therapeutic drugs.